The influence of preparation methods and doping on the electric-field-induced piezoelectric properties of potassium bismuth titanate (K₀.₅Bi₀.₅TiO₃) - Rakus, Piotr; Jędryka, Jarosław; Czaja, Piotr; Osińska, Katarzyna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
In this article, the influence of processing conditions, dopant type and poling temperature on the microstructure and piezoelectric behavior of lead-free K0.5Bi0.5TiO3 (KBT) ceramics is presented. Base KBT samples and those doped with Sr, Ca and Mn were synthesized via a solid-state reaction route, and examined with respect to their structural characteristics and electromechanical response. Particular emphasis was placed on elevated-temperature poling and its interaction with grain morphology and defect chemistry. SEM observations were used to identify dopant-dependent microstructural variations, while measurements of the d33 coefficient provided insight into how these factors influence efficiency of the poling process. The study demonstrates the importance of jointly optimizing synthesis parameters, dopant selection and poling conditions when tailoring the functional properties of KBT-based piezoelectric ceramics.